(sin theta+cos theta+1)(sin theta-1+cos theta)×sec theta cosec theta=2
Answers
Answered by
5
Step-by-step explanation:
Hope this helps u Please make me as a brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d46/3f749db6869d666216f8df055ce2f7ae.jpg)
Answered by
2
Step-by-step explanation:
= (Sin theta+Cos theta + 1)(Sin theta - 1+Costheta)
× Sec theta × Cosec theta
= {(Sin theta + Cos theta) + 1 } × {(Sin theta +
Cos theta) - 1 } × Sec theta × Cosec theta
= {(Sin theta + Cos theta)² - (1)²} × Sec theta
× Cosec theta
= {Sin²theta+Cos²theta + 2Sintheta*Cosectheta
- 1 } × Sec theta × Cosec theta
= { 1 + Sin 2theta - 1 } × Sec theta × Cosec theta
= Sin 2theta × Sec theta × Cosec theta
=2Sin theta *Cos theta × 1/Cos theta * Sin theta
= 2Sin theta * Cos theta / Sin theta* Cos theta
= 2
I hope it will help you
Similar questions
Social Sciences,
6 months ago
Hindi,
6 months ago
Chemistry,
6 months ago
Math,
1 year ago
Computer Science,
1 year ago